To solve 1 5/6 divided by 2 1/8, convert each number into an improper fraction, reciprocate the second fraction and multiply it with the first. The result is 8/6 which simplifies to 1 1/3.
To solve the problem of 1 5/6 divided by 2 1/8, we should first convert each mixed number into an improper fraction. The number 1 5/6 becomes 17/6 (because 1*6 + 5 = 11) and 2 1/8 becomes 17/8 (because 2*8 + 1 = 17). Then we transform the division into multiplication by using the reciprocal of the second fraction. This makes the problem 17/6 multiplied by 8/17. These two fractions multiply to simplifying to 1, leaving us with the answer of 8/6, which can be simplified to 1 1/3.
#SPJ2
Answer: $2.72
Step-by-step explanation: Multiply the amount of strawberries in this case 3.4 by the price per unit in this case $0.80 per pound.
Answer:
2.72
Step-by-step explanation:
The graph crosses the x-axis at x = 2 and x = -1 and touches the x-axis at x = 0.
The graph touches the x-axis at x = 2 and x = -1 and crosses the x-axis at x = 0.
The graph crosses the x-axis at x = -2 and x = 1 and touches the x-axis at x = 0.
O The graph touches the x-axis at x = -2 and x = 1 and crosses the x-axis at x = 0.
The correct option is,
⇒ The graph crosses the x-axis at x = -2 and x = 1 and touches the x-axis at x = 0.
A relation between a set of inputs having one output each is called a function. and an expression, rule, or law that defines a relationship between one variable (the independent variable) and another variable (the dependent variable).
Given function is,
f(x) = x⁴ + x³ - 2x²
Now, We can simplify as;
f(x) = x⁴ + x³ - 2x²
= x²(x² + x - 2)
= x²(x² + 2x - x - 2)
= x²[x(x + 2) - 1(x + 2)]
= x²(x + 2)(x - 1)
So the factored form of the polynomial function is,
f(x) = x²(x + 2)(x - 1)
For x - intercepts,
F(x) = x²(x + 2)(x - 1) = 0
x = -2, 1
This function has even multiplicity = 2 at x = 0.
Therefore, graph of the function will touch the x-axis at x = 0
And at other roots x = -2, 1 has odd multiplicity = 1, so the graph will cross the x-axis.
Thus, Option (3) will be the correct option.
Learn more about the function visit:
#SPJ7
Answer: C. The graph crosses the x-axis at x=-2 and x=1 & touches the x-axis at x=0
Step-by-step explanation:
You can tell this by factoring the equation to get the zeros. To start, pull out the greatest common factor.
f(x) = x^4 + x^3 - 2x^2
Since each term has at least x^2, we can factor it out.
f(x) = x^2(x^2 + x - 2)
Now we can factor the inside by looking for factors of the constant, which is 2, that add up to the coefficient of x. 2 and -1 both add up to 1 and multiply to -2. So, we place these two numbers in parenthesis with an x.
f(x) = x^2(x + 2)(x - 1)
Now we can also separate the x^2 into 2 x's.
f(x) = (x)(x)(x + 2)(x - 1)
To find the zeros, we need to set them all equal to 0
x = 0
x = 0
x + 2 = 0
x = -2
x - 1 = 0
x = 1
Since there are two 0's, we know the graph just touches there. Since there are 1 of the other two numbers, we know that it crosses there.